Poetry as Resistance: The Bengal Famine of 1770, Bangla Verses, and John Scott’s “Serim; or the Artificial Famine: An East-Indian Eclogue” - Islam, Monirul (Romanticism on the Net, 2021)
The present article explores the intersections of history, poetry, and empire in the context of Scott’s “Serim; or, the Artificial Famine: An East-Indian Eclogue.” With close analysis of the poem and the circumstances of the Bengal famine of 1770, it reads “Serim” as a poetic protest from the “metropole” against injustice committed by the British at the imperial periphery. Further, the article deliberates on the representation of the Bengalis in the poem while scrutinising orientalist tropes employed by Scott. With a final major turn, it weighs the significance of Scott’s eclogue as a cultural text documenting the first mass experience of colonial evil in India vis-à-vis some Bangla verses.